# Solve the equation -1x-6+12x^2=0

## 12x^2-x-6=0

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$x_1=0.75,\:x_2=-0.6667$

## Step by step solution

Problem

$12x^2-x-6=0$
1

To find the roots of a polynomial of the form $ax^2+bx+c$ we use the quadratic formula, where $a=12$, $b=-1$ and $c=-6$

$x =\frac{-b\pm\sqrt{b^2-4ac}}{2a}$
2

Substituting the values of the coefficients of the equation in the quadratic formula

$x=\frac{-1\left(-1\right)\pm \sqrt{{\left(-1\right)}^2-6\cdot 12\left(-4\right)}}{12\cdot 2}$
3

Multiply $-1$ times $-1$

$x=\frac{1\pm \sqrt{288+{\left(-1\right)}^2}}{24}$
4

Calculate the power

$x=\frac{1\pm \sqrt{288+1}}{24}$
5

Add the values $1$ and $288$

$x=\frac{1\pm \sqrt{289}}{24}$
6

Calculate the power

$x=\frac{1\pm 17}{24}$
7

To obtain the two solutions, divide the equation in two equations, one when $\pm$ is positive ($+$), and another when $\pm$ is negative ($-$)

$x_1=\frac{1+ 17}{24}\:\:,\:\:x_2=\frac{1- 17}{24}$
8

Simplifying

$x_1=0.75,\:x_2=-0.6667$
9

We found that the two real solutions of the equation are

$x_1=0.75,\:x_2=-0.6667$

$x_1=0.75,\:x_2=-0.6667$